Feeding patterns in Eubranchipus grubii (Dybowski 1860) (Branchiopoda: Anostraca) and its potential influence on the phytoplankton communities of vernal pools - Sofia Celewicz; Michał Jan Czyż; Bartłomiej Gołdyn (Journal of Limnology, 2018)
Filtration patterns in the fairy shrimp Eubranchipus grubii were analysed under laboratory conditions using water containing phytoplankton from their actual locality in western Poland. After 48 hours of feeding, we compared the structure of algal communities in water samples in treatments with males, females and control. The mean filtration rate for E. grubii was relatively high (14,488 mL h-1) in comparison to other crustacean filter feeders and was higher for females than for males. Fairy shrimps grazed effectively on all 11 dominant phytoplankton taxa and there was no sign of overall preferences with regard to taxon, cell volume, length or shape. Female fairy shrimps removed significantly more cells of three taxa (Cryptomonas erosa, C. ovata and Trachelomonas volvocina). The differences between sexes did not depend on the cell volume or length of particular phytoplankton taxa but were significantly related to their initial abundance, initial biomass and shape. The higher the abundance and biomass of the algal taxa, the more intensively it was grazed by females than by males. Females were also observed to graze more on spherical and elongated cells. In conclusion, our results show E. grubii to be an effective, generalist filter feeder capable of significantly influencing the phytoplankton community of a vernal pool. Possible implications of such grazing pressure are also discussed.